The Da Vinci Code in the Academy. - Bowers, Bradley R. (Bradley Ray), 1956- (Cambridge Scholars Publishing, 2008)
As millions of readers worldwide react to Dan Brownâs The Da Vinci Code, so do many scholars. The novel has become a proxy debate for two compelling scholarly and social issues of our time: the feminist/post-feminist challenge to patriarchal authority.